2020
DOI: 10.1002/1878-0261.12739
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of PRKDC mutations and association with response to immune checkpoint inhibitors in solid tumors

Abstract: Predictive biomarkers of response to immune checkpoint inhibitors (ICI) help to identify cancer patients who will benefit from immunotherapy. Protein kinase, DNA‐activated, catalytic subunit (PRKDC) is an important gene for DNA double‐strand break (DSB) repair and central T‐cell tolerance. We aimed to investigate the association between PRKDC mutations and tumor mutation burden (TMB), tumor microenvironment (TME), and response to ICI. Whole‐exome sequencing data of 4023 solid tumor samples from the Cancer Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 36 publications
(53 reference statements)
0
28
0
Order By: Relevance
“…The mutation rate of PRKDC and the expression level of DNA-PKcs in various tumors are quite different. Chen et al [ 37 ] conducted statistical analysis on the mutation rate of PRKDC as reported in the Cancer Genome Atlas (TCGA) and the Chinese population database; the authors found that PRKDC had a high mutation rate in several tumors, such as colorectal cancer, gastric cancer, and endometrial cancer, with a high correlation with microsatellite instability. In the TCGA database, PRKDC mutations were found in 51 (9.66%) of 528 colorectal cancers, 42 (9.63%) of 436 gastric cancers, and 23 (9.27%) of 248 endometrial cancers.…”
Section: Relationship Between Prkdc and Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…The mutation rate of PRKDC and the expression level of DNA-PKcs in various tumors are quite different. Chen et al [ 37 ] conducted statistical analysis on the mutation rate of PRKDC as reported in the Cancer Genome Atlas (TCGA) and the Chinese population database; the authors found that PRKDC had a high mutation rate in several tumors, such as colorectal cancer, gastric cancer, and endometrial cancer, with a high correlation with microsatellite instability. In the TCGA database, PRKDC mutations were found in 51 (9.66%) of 528 colorectal cancers, 42 (9.63%) of 436 gastric cancers, and 23 (9.27%) of 248 endometrial cancers.…”
Section: Relationship Between Prkdc and Tumormentioning
confidence: 99%
“…Immunotherapies have received increasing attention in recent years, and among the most important ones are the immune checkpoint inhibitor (ICI) therapies [ 70 , 71 ]. Currently, an important factor in predicting the response to ICIs is tumor mutation burden (TMB) [ 37 ], which refers to the number of nonsynonymous mutations per million bases of the tumor cell genome. The damage to the DDR system is closely related to the TMB, and a functional defect of the DDR system leads to increased genomic instability and accumulation of mutations in cells [ 37 ].…”
Section: Prkdc and Tumor Treatmentmentioning
confidence: 99%
“…These findings highlight PRKDC mutation as a potential biomarker for immunotherapy. Moreover, Chen et al recently investigated the association between PRKDC mutations and tumor mutation burden (TMB), tumor microenvironment (TME), and response to ICI by integrated analysis of sequencing data of solid tumors in TCGA ( n = 4023) and Geneplus ( n = 3877) [ 57 ]. They showed that PRKDC mutant tumors have significantly higher TMB than that of PRKDC wild-type tumors.…”
Section: Dna-pkcs In Immunitymentioning
confidence: 99%
“…Further, solid tumors harboring PRKDC mutations were enriched in tumor immunogenicity microenvironments, such as CD8+ T cells, NK (natural killer) cells, and chemokines. Importantly, PRKDC mutations were associated with better survival in patients after ICI treatment [ 57 , 58 ]. These results support the use of PRKDC mutations as a stratification marker for immunotherapy.…”
Section: Dna-pkcs In Immunitymentioning
confidence: 99%
“…We found that over 18% of UCEC patients and about 12% of STAD patients presented alteration in PRKDC and the alteration correlates with better survival. In a recent study (31), PRKDC mutation was found to be related to higher TMB, elevated mRNA levels of immunity-related genes as well as improved response to ICI (immune checkpoint inhibitor) treatments in tumor individual. Another publication also discovered that PRKDC mutation was linked to an advanced TMB and MSI states in tumors, and knocked down PRKDC or used a DNA-PKcs inhibitor might improve ICI e cacy (32).…”
Section: Discussionmentioning
confidence: 98%